2020
DOI: 10.3390/vaccines8010081
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Encephalitis Virus Vaccines Contain Non-Structural Protein 1 Antigen and May Elicit NS1-Specific Antibody Responses in Vaccinated Individuals

Abstract: Vaccination against tick-borne encephalitis (TBE) is based on the use of formalin-inactivated, culture-derived whole-virus vaccines. Immune response following vaccination is primarily directed to the viral envelope (E) protein, the major viral surface antigen. In Europe, two TBE vaccines are available in adult and pediatric formulations, namely FSME-IMMUN® (Pfizer) and Encepur® (GlaxoSmithKline). Herein, we analyzed the content of these vaccines using mass spectrometry (MS). The MS analysis revealed that the E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
2
32
1
Order By: Relevance
“…The results show that FSME-Immun is the only vaccine that elicits an NS1-specific antibody response in mice. Why the Encepur vaccine does not elicit an NS1-specific antibody response, despite containing detectable levels of NS1 antigen [8], remains enigmatic. After FSME-Immun vaccination, the NS1-specific response is much weaker compared Our mouse experiments have shown that three doses representing the complete vaccination scheme are insufficient to elicit detectable levels of NS1-specific antibodies, and this could explain why there was no detection of NS1 antibodies in studies involving participants who received only the basic vaccination scheme consisting of three doses of the vaccine [7,[9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…The results show that FSME-Immun is the only vaccine that elicits an NS1-specific antibody response in mice. Why the Encepur vaccine does not elicit an NS1-specific antibody response, despite containing detectable levels of NS1 antigen [8], remains enigmatic. After FSME-Immun vaccination, the NS1-specific response is much weaker compared Our mouse experiments have shown that three doses representing the complete vaccination scheme are insufficient to elicit detectable levels of NS1-specific antibodies, and this could explain why there was no detection of NS1 antibodies in studies involving participants who received only the basic vaccination scheme consisting of three doses of the vaccine [7,[9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…First of all, the presence of IgG antibodies against TBEV may be a result from previous infection and/or vaccination. Recently, it has been suggested that the presence of TBEV non-structural (NS)-1 antibodies may discriminate between TBEV-infected and TBEV-vaccinated individuals [ 39 , 40 ], but this data has been challenged [ 41 ], and presently, there is no standardized way of determining whether detected TBEV-specific IgG antibodies are a consequence of infection or vaccination. Secondly, the interpretation of the serology test is complicated since the result can be influenced by cross-reacting antibodies from other flaviviruses by vaccination or infection.…”
Section: Resultsmentioning
confidence: 99%
“…Patients and healthy controls received up to three doses of FSME Immun ® intramuscularly—first at baseline at enrollment, which took place 11–13 months after HSCT, second after four weeks and third after 9–12 months. Each dose of FSME Immun ® contains 2.4 µg of formalin-inactivated TBE antigen (with the major constituent virus envelope protein E [ 15 ]) of the European TBEV subtype strain Neudörfl, human albumin as stabilizer and aluminum hydroxide as an adjuvant. Peripheral blood mononuclear cells (PBMCs) were sampled at baseline before the first vaccination, one week after the second and one week after the third vaccination.…”
Section: Methodsmentioning
confidence: 99%